Forest property insurance: an application to mediterranean woodlands - Pinheiro, António C. (2013)
Fire is the biggest forest enemy in many countries, especially in those that have dry and hot climates. Fire destroys biomass and makes forest production a very risky business. Forest insurance could decrease fire risk and would contribute to make forest activities more profitable. Nowadays, in many countries, it is not easy to find companies that want to insure forests stands. The most important reasons to explain this fact are the followings. First, in many countries, forest insurance is not mandatory; so many farmers don’t make it. This increases the risk premium that insurance companies ask for those that were willing to make the insurance contract. Second, insurance companies need to have models based on desegregated and reliable data that allow them estimating the probability of fire occurrences. Finally, it is very difficult for insurer to estimate the real value of the stands (forests) because their values vary from species to species and for the same species with the age and market prices. So, it is difficult for insurer to practice fair and reasonable insurance premiums. The main objective of this paper is to present simple models that help to estimate “fair” insurance risk premiums, contributing in this way to make forest business more appealing and sustainable.